Mucosal Immunoregulatory Properties of Tsukamurella inchonensis to Reverse Experimental Food Allergy - Smaldini, Paola Lorena (2021)
The intestinal mucosa is lined by epithelial cells, which are key cells to sustain gut homeostasis. Food allergy is an immune-mediated adverse reaction to food, likely due to defective regulatory circuits. Tsukamurella inchonensis is a non-pathogenic bacterium with immunomodulatory properties. We hypothesize that the anti-inflammatory effect of dead T. inchonensis on activated epithelial cells modulates milk allergy through the restoration of tolerance in a mouse model. Epithelial cells (Caco-2 and enterocytes from mouse gut) and macrophages were stimulated with T. inchonensis and induction of luciferase under the NF-kB promoter, ROS and cytokines production were studied. Balb/cmice weremucosally sensitized with cow´s milk proteins plus cholera toxin and orally challenged with the allergen to evidence hypersensitivity symptoms. After that, mice were orally administered with heatkilled T. inchonensis as treatment and then challenged with the allergen. The therapeutic efficacy was in vivo (clinical score and cutaneous test) and in vitro (serum specific antibodies and cytokines-ELISA, and cell analysis-flow cytometry) evaluated. Heat-killed T. inchonensis modulated the induction of pro-inflammatory chemokines, with an increase in antiinflammatory cytokines by intestinal epithelial cells and by macrophages with decreased OX40L expression. In vivo, oral administration of T. inchonensis increased the frequency of lamina propria CD4+CD25+FoxP3+ T cells, and clinical signs were lower in T. inchonensistreated mice compared with milk-sensitized animals. In vivo depletion of Tregs (anti-CD25) abrogated T. inchonensis immunomodulation. In conclusion, these bacteria suppressed the intestinal inflammatory immune response to reverse food allergy.